The ends of harm the moral foundations of criminal law - Tadros, Victor (Oxford : Oxford University Press, 2011)
How can the brutal and costly enterprise of criminal punishment be justified? This text makes a contribution to the philosophical literature and debate on the morality of punishing, arguing that punishment is justified in the duties that offenders incur as a result of their wrongdoing.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Criminal law -- Moral and ethical aspects; Punishment -- Moral and ethical aspects; Criminal law -- Philosophy; Punishment -- Philosophy